Seleção socioeconômica: legitimação da desigualdade social na sociedade capitalista - um estudo dos fundamentos sócio-históricos de sua operação na política social e no Serviço Social - Pitarello, Marli (2013)
This thesis objective is to provide a basis for the intervention of the professional social worker in socioeconomic selection. In social organizations, socioeconomic selection is an instrument used by the social worker, as an employee, to enable the benefits and social services demanding population to qualify for access to goods and services, often constitutionally provided, but denied in practice as universal social right. Under these conditions, the socioeconomic selection, as instrument of social policy operated by social workers in almost all social organizations taken as socio-occupational profession spaces is what this study is concerned with. The analysis undertaken located the emergence of selectivity and its grounds, which were incorporated into the historically constructed social protection proposals, particularly from the sixteenth and seventeenth centuries on, in Western Europe, and still present today under the aegis of neoliberal capitalism. To reach the selectivity deeper significance involved the analysis of social rights in the face of today universalization and targeting of social policies, as well as the sense of the compensatory conditions as part of this selectivity. The research further explains the reasons attributed to socioeconomic selection when it has become a social worker activity with the emergence and institutionalization of Social Work in the United States, Western Europe and Brazil, highlighting the role of the Catholic Church in the expansion of Social Work on the world stage. An examination of the relationship between socioeconomic selection, Social Policy and Social Work reveals the nature, the usefulness and significance of this selection, both in the context of social policy, as in the social workers involvement in selection processes, in the sense of its social legitimacy in capitalist society. Discussing this articulation in the work and training of social workers, through the contribution of literature and a qualitative study conducted with social service works in Brazil and Portugal, the study concludes that, despite the struggles undertaken by workers, changes in the access to social services and benefits are still small, and that the foundations of socioeconomic selection practiced by the early social workers are still strongly present. Today, faced with the global trend of targeting of social policy, Portugal and Brazil being two examples, the selectivity of access of social policy has increased, indicating the need for further reflection and the pursuit of constructing responses in order to meet the interests of workers or those who depend on work to live